Vanadium-based catalyst as well as preparation method and application thereof
By using a resistive vanadium-based catalyst with a modified diatomaceous earth support, the problem of the catalyst bed lamellar is solved, and the effect of reducing the loading amount, reducing the pressure drop and improving the conversion rate is achieved.
Patent Information
- Application Number
- CN202311366228.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing vanadium-based catalysts cannot solve the problem of the catalyst bed latching, resulting in an increase in the pressure drop of the device and affecting long-term operation.
Modified diatomaceous earth is used as a support, supported by active components such as vanadium pentoxide and potassium sulfate and co-active components, and the adhesive montmorillonite is added through kneading to enhance the bone strength and catalytic activity of the support.
Under the premise of achieving the same performance, the loading volume of the catalyst is reduced by about 35%, the pressure drop of the sulfuric acid device is reduced, the total conversion rate of SO2 is increased, and the service life of the catalyst is significantly improved.
Smart Images

Figure BDA0004504414220000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a vanadium-based catalyst and a preparation method and application thereof. Background Art
[0002] The standard requirements for motor gasoline are getting higher and higher, and the content of olefins and aromatics in gasoline is constantly decreasing, resulting in a decrease in the octane number of gasoline. With the strengthening of people's environmental awareness, environmentally harmful gasoline anti-knock agents such as MTBE are increasingly resisted. In order to maintain the octane number of gasoline, alkylate oil has become a popular choice. At present, most alkylation units use sulfuric acid process, which will produce a large amount of alkylation waste acid. The waste acid regeneration unit is an environmental protection device supporting the alkylation unit. Its process mainly involves burning and cracking waste sulfuric acid with w (H2SO4) 89%-90.5% through a waste acid cracking furnace, converting SO2 in the cracking gas into SO3 through a vanadium-based catalyst, and finally condensing it into commercial sulfuric acid with w (H2SO4) 98%-99.2%. The regenerated product sulfuric acid is returned to the alkylation unit as a catalyst for sulfuric acid alkylation reaction and recycled. However, the dust content in the waste acid cracking gas is very high, which can easily cause the bed layer of the subsequent catalyst to become hardened.
[0003] Vanadium-based catalysts are used in sulfuric acid production devices to oxidize SO2 into SO3. Traditional vanadium-based catalysts are vanadium-potassium (sodium)-silicon systems, with vanadium pentoxide as the active component, potassium sulfate and sodium sulfate as additives, and Shandong diatomite, Northeast diatomite or a mixture of the two as carriers. The preparation method of the vanadium-based catalyst includes: dissolving KOH with steam, and preparing a KVO3 and KOH mixed solution (referred to as vanadium water) that meets the requirements with V2O5 under hot boiling conditions, and then neutralizing the vanadium water with sulfuric acid to obtain V2O5 and K2SO4 colloidal precipitates; adding the colloidal precipitate, the additive, refined diatomite, etc. to a roller and mixing them evenly, rolling them tightly to become a plastic material, and then making a vanadium-based catalyst through processes such as extrusion, drying, roasting, screening and packaging. However, the vanadium-based catalyst cannot solve the problem of catalyst bed compaction, so it is urgent to develop an anti-impedance vanadium-based catalyst. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of catalyst bed compaction in the prior art, and to provide a vanadium-based catalyst and a preparation method and application thereof. The vanadium-based catalyst is an anti-blocking vanadium-based catalyst, and the loading amount of the catalyst is small. Under the premise of achieving the same performance, the overall loading amount of the catalyst can be reduced by 35%, which greatly reduces the pressure drop of the sulfuric acid device. The catalyst is particularly suitable for a waste acid cracking sulfuric acid production device with a high impurity content in the raw gas, which brings great advantages to long-term operation.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a vanadium-based catalyst, which comprises modified diatomaceous earth and an active component and a co-active component loaded on the modified diatomaceous earth; wherein the crystalline SiO2 content of the modified diatomaceous earth is not less than 90%, the active component comprises vanadium pentoxide, and the co-active component comprises potassium sulfate.
[0006] A second aspect of the present invention provides a method for preparing a vanadium-based catalyst, the preparation method comprising:
[0007] (1) separating and purifying diatomaceous earth in a hydrocyclone separator to obtain diatomaceous earth powder, and subjecting the diatomaceous earth powder to a first calcination to obtain modified diatomaceous earth;
[0008] (2) neutralizing vanadium water prepared with potassium hydroxide and vanadium pentoxide with sulfuric acid to obtain a reaction product;
[0009] (3) The reaction product is mixed with the modified diatomaceous earth, a binder and an optional hydroxide, and the mixture is kneaded, extruded, dried and subjected to a second calcination to obtain a vanadium-based catalyst.
[0010] The third aspect of the present invention provides use of the vanadium-based catalyst described in the first aspect or the vanadium-based catalyst prepared by the preparation method described in the second aspect in wet production of sulfuric acid.
[0011] The fourth aspect of the present invention provides a method for preparing wet sulfuric acid, in the presence of the vanadium-based catalyst described in the first aspect or the vanadium-based catalyst prepared by the preparation method described in the second aspect, SO2 in the raw gas is catalytically oxidized to produce SO3, which is then condensed to obtain concentrated sulfuric acid.
[0012] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0013] 1) The vanadium-based catalyst of the present invention is an resistant vanadium-based catalyst, and the loading amount of the catalyst is small. Under the premise of achieving the same performance, the overall loading amount of the catalyst can be reduced by 35%, which greatly reduces the pressure drop of the sulfuric acid device. It is particularly suitable for a waste acid cracking sulfuric acid production device with a high impurity content in the raw gas, and has great advantages for long-term operation.
[0014] 2) The vanadium-based catalyst of the present invention is used to prepare sulfuric acid by cracking waste acid with a high impurity content in raw gas, which can reduce the overall catalyst loading by 35%, thereby reducing the bed pressure drop and improving the overall conversion rate of SO2. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] The first aspect of the present invention provides a vanadium-based catalyst, which includes modified diatomaceous earth and an active component and an alkali metal auxiliary agent loaded on the modified diatomaceous earth; wherein the crystalline SiO2 content of the modified diatomaceous earth is not less than 90%, the active component includes vanadium pentoxide, and the auxiliary active component includes potassium sulfate.
[0017] According to the present invention, the vanadium-based catalyst uses modified diatomaceous earth as a carrier, the crystalline SiO2 content of which is not less than 90%, and the carrier strength is higher than that of ordinary diatomaceous earth.
[0018] The active component of the vanadium-based catalyst of the present invention is vanadium pentoxide, which is loaded on a diatomaceous earth carrier in a liquid molten state when activated, and is a liquid-phase loaded catalyst. Adding auxiliary active components such as potassium sulfate can reduce the melting temperature, which is more conducive to improving the low-temperature activity of the vanadium-based catalyst.
[0019] In some embodiments of the present invention, the average particle size of the modified diatomaceous earth is 0.3-1 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm and any value in the range consisting of any two values, preferably 0.6-1 μm.
[0020] In some embodiments of the present invention, the method for preparing the modified diatomite comprises: separating and purifying the diatomite in a hydrocyclone separator to obtain diatomite powder, and then performing a first calcination on the diatomite powder to obtain the modified diatomite.
[0021] According to the present invention, separation and purification are carried out in a hydrocyclone separator, impurities such as Fe2O3, Al2O3, CaO, MgO, etc. are effectively removed and the bulk density is reduced, the purity of SiO2 is improved, the crystalline SiO2 content reaches more than 90%, and the strength of the catalyst carrier can be improved.
[0022] The present invention adopts a physical process to modify the diatomite, thereby avoiding the generation of waste water by the acid washing method adopted in the traditional refining, and makes the structure more stable through the high temperature treatment of the first calcination.
[0023] In some embodiments of the present invention, the diatomaceous earth is of the genus Melosomum; preferably, the diatomaceous earth is selected from one or more of Zhejiang diatomaceous earth, Yunnan diatomaceous earth and Changbai diatomaceous earth.
[0024] The diatomaceous earth used in the present invention is of the genus Melosomum, whose shell porosity is the highest among diatomaceous earths, and whose pore volume, main pore diameter and specific surface area are all larger than those of other genera, especially the inner surface.
[0025] In some embodiments of the present invention, the shell of the modified diatomaceous earth is a hollow cylinder, the shells are connected by small thorns on the periphery of the shell to form a chain-like group, and the holes on the cylinder surface are connected to the central hole.
[0026] Furthermore, under an electron microscope, there are 6-9 rows of holes within 10 μm and 6-8.5 small holes vertically.
[0027] According to the present invention, the modified diatomite is formed into a hollow cylinder, which has the best strength and is not easy to break from a mechanical point of view. During the processing, it can better maintain its original shape, so as a carrier, it can form a group with well-developed pores, good strength, and good mass and heat transfer.
[0028] In some embodiments of the present invention, in the vanadium-based catalyst, the molar ratio of potassium element to vanadium element is 2-4:1.
[0029] In the present invention, the molar ratio of potassium to vanadium is also referred to as potassium-vanadium ratio. A too small potassium-vanadium ratio will affect the activity of the vanadium-based catalyst, while a too large potassium-vanadium ratio will increase production costs.
[0030] In some embodiments of the present invention, the vanadium-based catalyst further comprises a promoter, and the promoter is selected from one or more of rubidium sulfate, cesium sulfate and sodium sulfate.
[0031] In the present invention, the additive can further improve the low-temperature activity of the vanadium-based catalyst and reduce the activation temperature of the vanadium-based catalyst.
[0032] In some embodiments of the present invention, based on 100% of the total weight of the catalyst, the vanadium-based catalyst comprises: 60-75wt% modified diatomaceous earth, 6-8.5wt% vanadium pentoxide, 12-30wt% potassium sulfate, 3.5-10wt% additive and 0.5-2.5wt% binder.
[0033] In some preferred embodiments of the present invention, based on 100% of the total weight of the catalyst, the vanadium-based catalyst comprises: 65-70wt% of modified diatomaceous earth, 6.5-8wt% of vanadium pentoxide, 15-22wt% of potassium sulfate, 4-8wt% of an additive and 1-2wt% of a binder.
[0034] In some embodiments of the present invention, the binder is selected from one or more of montmorillonite, attapulgite and methyl cellulose.
[0035] The inventor of the present application has found through research that the presence of a small amount of impurities has nothing to do with the activity of the catalyst, but has a great relationship with the mechanical strength and service life of the catalyst. Diatomaceous earth without such impurities cannot become a good carrier even if the SiO2 content is very high, so that the catalyst is often ineffective due to pulverization or sintering during use. Therefore, the present invention adopts a kneading method to add the binder montmorillonite to the active component and the carrier, which is more effective than the traditional mixing and grinding method to fully combine the active component and the carrier, enhance the carrier's bone strength, and can prepare a catalyst with higher catalytic activity.
[0036] In some embodiments of the present invention, the radial crushing resistance of the vanadium-based catalyst is ≥70 N / cm, and the attrition rate is ≤3%.
[0037] In the present invention, the radial crushing resistance is tested by the method for testing the crushing resistance of fertilizer catalyst particles in HG / T 2782, and the attrition rate is tested by the method for testing the attrition rate of fertilizer catalyst particles in HG / T 2976.
[0038] In some embodiments of the present invention, the vanadium-based catalyst is a plum blossom-shaped porous catalyst with 3-10 pores.
[0039] In the present invention, the catalyst is made into a porous plum blossom shape with 3-10 holes, which can effectively reduce the bed pressure drop.
[0040] A second aspect of the present invention provides a method for preparing a vanadium-based catalyst, the preparation method comprising:
[0041] (1) separating and purifying diatomaceous earth in a hydrocyclone separator to obtain diatomaceous earth powder, and subjecting the diatomaceous earth powder to a first calcination to obtain modified diatomaceous earth;
[0042] (2) neutralizing the vanadium water of potassium hydroxide and vanadium pentoxide with sulfuric acid to obtain a reaction product;
[0043] (3) The reaction product obtained in step (2) is mixed with the modified diatomaceous earth, optional auxiliary agents and adhesives, and subjected to kneading, extrusion, drying and second calcination to obtain a vanadium-based catalyst.
[0044] In the present invention, organic matter in diatomaceous earth is removed by the first calcination, thereby further improving the purity of SiO2 and further improving the strength of the catalyst carrier.
[0045] In some embodiments of the present invention, the crystalline SiO2 content of the modified diatomaceous earth is not less than 90%.
[0046] In some embodiments of the present invention, in the vanadium water of step (2), the molar ratio of potassium element to vanadium element is 2-4:1.
[0047] In some embodiments of the present invention, the mass ratio of the modified diatomaceous earth, the auxiliary agent and the adhesive is 60-75:3.5-10:0.5-2.5.
[0048] In some embodiments of the present invention, the mass ratio of the modified diatomaceous earth to vanadium pentoxide is 60-75:6-8.5.
[0049] In some embodiments of the present invention, the processing capacity of the hydrocyclone separator is 0.25-2.5m 3 / h, the pulp inlet pressure is 0.2-1MPa, and the classification fineness is 0.3-1μm.
[0050] In some embodiments of the present invention, the temperature of the first calcination is 350° C.-500° C., and the time is 1-2 hours.
[0051] In some embodiments of the present invention, the second calcination is performed at a temperature of 580° C. to 650° C. for a time of 1 to 2 hours.
[0052] In some embodiments of the present invention, the second calcination is carried out in a vertical tubular furnace and water vapor is continuously and uniformly introduced into the calcination inlet.
[0053] The inventors have found through research that compared with calcination without humidified air, the humidified air in the second calcination process can shift the pore size distribution toward the large pores. Therefore, the introduction of water vapor and humidified air in the calcination process has a pore expansion effect on the carrier. The average pore size after pore expansion is about 150-500nm, which is beneficial for the reactant molecules to diffuse in the pores to reach the active centers on the inner surface of the catalyst.
[0054] In some embodiments of the present invention, the element molar ratio of potassium to vanadium is 2-4.
[0055] In some embodiments of the present invention, the mass ratio of the modified diatomaceous earth, the binder and the sodium sulfate is 79.5-90:0.5-2.5:3-7.
[0056] In some embodiments of the present invention, the mass ratio of the modified diatomaceous earth to vanadium pentoxide is 79.5-90:6-8.5.
[0057] In some embodiments of the present invention, the diatomaceous earth is of the genus Melosomum; preferably, the diatomaceous earth is selected from one or more of Zhejiang diatomaceous earth, Yunnan diatomaceous earth and Changbai diatomaceous earth.
[0058] The diatomaceous earth used was of the genus Melosomum, which has the highest shell porosity among diatomaceous earths, and its pore volume, main pore diameter and specific surface area are larger than those of other genera, especially the inner surface.
[0059] In some embodiments of the present invention, the auxiliary agent is selected from one or more of rubidium sulfate, cesium sulfate and sodium sulfate.
[0060] In some embodiments of the present invention, the binder is selected from one or more of montmorillonite, attapulgite and methyl cellulose.
[0061] The third aspect of the present invention provides use of the vanadium-based catalyst described in the first aspect or the vanadium-based catalyst prepared by the preparation method described in the second aspect in wet production of sulfuric acid.
[0062] The fourth aspect of the present invention provides a method for preparing wet sulfuric acid, in the presence of the vanadium-based catalyst described in the first aspect or the vanadium-based catalyst prepared by the preparation method described in the second aspect, SO2 in the raw gas is catalytically oxidized to produce SO3, which is then condensed to obtain concentrated sulfuric acid.
[0063] In some embodiments of the present invention, the volume percentage of SO2 in the raw gas is 1-9%.
[0064] In some embodiments of the present invention, the feed gas is spent acid cracking gas or acid gas.
[0065] Preferably, the acid mist content of the waste acid cracking gas is less than 0.11 g / Nm 3 , mineral dust content <0.01g / Nm 3 .
[0066] The catalyst of the present invention can catalytically treat acid mist with a content of 0.03-0.11 g / Nm 3 , mineral dust content 0.005-0.01g / Nm 3 The existing catalyst can only process the acid mist content of less than 0.03g / Nm 3 , mineral dust content <0.005g / Nm 3 of spent acid cracking gas.
[0067] In some embodiments of the present invention, the inlet temperature of the feed gas is 370°C-440°C.
[0068] In some embodiments of the present invention, the filling factor of the vanadium-based catalyst in the wet sulfuric acid production device is 500 L / (t·d).
[0069] The present invention is described in detail below through preparation examples and examples, but the protection scope of the present invention is not limited to the following description.
[0070] In the following preparation examples, embodiments and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels.
[0071] The diatomite raw material was purchased from the American EP Company, CELATOM MN-3 model, with an average particle size of 11 μm and an average pore size of 95 nm.
[0072] Preparation Example 1
[0073] The diatomite raw material is added to a hydrocyclone separator for centrifugal impurity removal, the slurry inlet pressure is 0.3Mpa, the classification fineness is 0.5μm, and the impurity-removed raw material is dried and calcined at 350°C for 1h to obtain modified diatomite S1; after testing, the crystalline SiO2 content of the modified diatomite S1 is 90.1%, and the average particle size is 1μm.
[0074] Preparation Example 2
[0075] The diatomite raw material is added to a hydrocyclone separator for centrifugal impurity removal, the slurry inlet pressure is 0.5 MPa, the classification fineness is 0.4 μm, and the raw material after impurity removal is dried and calcined at 380°C for 1 hour to obtain modified diatomite S2; after testing, the crystalline SiO2 content of the modified diatomite S2 is 90.5%, and the average particle size is 0.8 μm.
[0076] Preparation Example 3
[0077] The diatomite raw material is added to a hydrocyclone separator for centrifugal impurity removal, the slurry inlet pressure is 0.7 MPa, the classification fineness is 0.3 μm, and the impurity-removed raw material is dried and calcined at 400°C for 1 hour to obtain modified diatomite S3; after testing, the crystalline SiO2 content of the modified diatomite S3 is 92%, and the average particle size is 0.4 μm.
[0078] Example 1
[0079] 18.32 g of potassium hydroxide and 8.5 g of vanadium pentoxide are dissolved in 25 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 260 g / L; 32.7 mL of vanadium water is neutralized with 10.32 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 2.5 g of cesium sulfate, and then added to a kneader with 7 g of sodium sulfate, 65 g of modified diatomaceous earth S1 obtained in Preparation Example 1 and 2.5 g of montmorillonite, and fully kneaded, water is added to make it a plastic material, and then it is extruded into a 4-hole plum blossom-shaped catalyst, dried, and continuously introduced with water vapor at a temperature of 650°C at the calcination inlet for calcination for 1 hour to prepare 100 g of vanadium-based catalyst C1.
[0080] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 88%, the strength of the vanadium-based catalyst C1 is 90 N / cm, and the average pore size of the catalyst is 250 nm.
[0081] Example 2
[0082] 14.11 g of potassium hydroxide and 6.5 g of vanadium pentoxide are dissolved in 27 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 240 g / L; 27 mL of vanadium water is taken and neutralized with 4 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 0.5 g of rubidium sulfate, and then added into a kneader with 5 g of sodium sulfate, 70.5 g of modified diatomaceous earth S2 obtained in Preparation Example 2 and 1.5 g of montmorillonite, and fully kneaded, water is added to make it a plastic material, and then it is extruded into a 3-hole plum blossom-shaped catalyst, dried, and continuously introduced into the calcination inlet at a temperature of 620°C for calcination for 1.5 hours to prepare 100 g of vanadium-based catalyst C2.
[0083] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 89%, the strength of the vanadium-based catalyst C2 is 92 N / cm, and the average pore size of the catalyst is 280 nm.
[0084] Example 3
[0085] 14.78 g of potassium hydroxide and 6 g of vanadium pentoxide are dissolved in 27 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 220 g / L; 27.2 mL of vanadium water is taken and neutralized with 6.3 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution and 1 g of cesium sulfate are evenly mixed, and then added into a kneader with 3 g of sodium sulfate, 68 g of modified diatomaceous earth S3 obtained in Preparation Example 3 and 1 g of montmorillonite, and fully kneaded, water is added to make it a plastic material, and then it is extruded into a 5-hole plum blossom-shaped catalyst, dried, and continuously introduced into the calcination inlet at 600°C for calcination for 1 hour to prepare 100 g of vanadium-based catalyst C3.
[0086] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 90.5%, the strength of the vanadium-based catalyst C3 is 105 N / cm, and the average pore size of the catalyst is 300 nm.
[0087] Example 4
[0088] 15 g of potassium hydroxide and 7 g of vanadium pentoxide are dissolved in 30 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 230 g / L; 30.4 mL of vanadium water is neutralized with 6.3 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 1.5 g of rubidium sulfate, and then added with 6 g of cesium sulfate, 67.5 g of modified diatomaceous earth S1 obtained in Preparation Example 2 and 1.5 g of montmorillonite in a kneader and fully kneaded, water is added to make it a plastic material, and then it is extruded into a 6-hole plum blossom-shaped catalyst, dried, and continuously introduced with water vapor at a temperature of 580°C at the calcination inlet for calcination for 2 hours to prepare 100 g of vanadium-based catalyst C4.
[0089] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 88.5%, the strength of the vanadium-based catalyst C4 is 91N / cm, and the average pore size of the catalyst is 350nm.
[0090] Example 5
[0091] 17.1 g of potassium hydroxide and 7.5 g of vanadium pentoxide are dissolved in 31 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 247 g / L; 30.3 mL of vanadium water is neutralized with 8.2 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 2 g of cesium sulfate, and then added with 6.5 g of sodium sulfate, 68.7 g of modified diatomaceous earth S1 obtained in Preparation Example 3 and 2 g of montmorillonite in a kneader and fully kneaded, water is added to make it a plastic material, and then it is extruded into an 8-hole plum blossom-shaped catalyst, dried, and continuously introduced with water vapor at a temperature of 620°C at the calcination inlet for calcination for 1 hour to prepare 100 g of vanadium-based catalyst C5.
[0092] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 90.5%, the strength of the vanadium-based catalyst C5 is 110 N / cm, and the average pore size of the catalyst is 375 nm.
[0093] Example 6
[0094] 17.24 g of potassium hydroxide and 8 g of vanadium pentoxide are dissolved in 32 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 250 g / L; 32 mL of vanadium water is neutralized with 8 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 2.2 g of cesium sulfate, and then added with 5.5 g of sodium sulfate, 68.5 g of modified diatomaceous earth S1 obtained in Preparation Example 2 and 2.2 g of montmorillonite to a kneader for thorough kneading, water is added to make it a plastic material, and then it is extruded into a 9-hole plum blossom-shaped catalyst, which is dried and calcined at 640°C for 2 hours to prepare 100 g of vanadium-based catalyst C6.
[0095] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 86.5%, the strength of the vanadium-based catalyst C6 is 78 N / cm, and the average pore size of the catalyst is 410 nm.
[0096] Example 7
[0097] 15.74 g of potassium hydroxide and 7.3 g of vanadium pentoxide are dissolved in 29 mL of water to prepare vanadium water with a vanadium pentoxide concentration of 255 g / L; 28.6 mL of vanadium water is neutralized with 7.5 mL of sulfuric acid solution to obtain a mixed solution of V2O5 and K2SO4; the mixed solution is evenly mixed with 0.8 g of rubidium sulfate, and then added with 5 g of sodium sulfate, 69 g of modified diatomaceous earth S1 obtained in Preparation Example 3 and 1.8 g of montmorillonite in a kneader and fully kneaded, water is added to make it a plastic material, and then it is extruded into a 10-hole plum blossom-shaped catalyst, dried, and calcined at 645°C for 1 hour to prepare 100 g of vanadium-based catalyst C7.
[0098] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 87%, the strength of the vanadium-based catalyst C7 is 80 N / cm, and the average pore size of the catalyst is 368 nm.
[0099] Example 8
[0100] The vanadium-based catalyst C8 was prepared according to the method of Example 4, except that the added amount of the modified diatomaceous earth S2 obtained in Preparation Example 1 was 70 g, and the rest was the same as Example 4.
[0101] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 88.5%, the strength of the vanadium-based catalyst C8 is 92N / cm, and the average pore size of the catalyst is 355nm.
[0102] Example 9
[0103] The vanadium-based catalyst C9 was prepared according to the method of Example 5, except that the amount of modified diatomite S3 obtained in Preparation Example 1 was 75 g, and water vapor was continuously introduced into the calcination inlet at a temperature of 620° C. for calcination for 2 h, and the rest was the same as Example 5. The heat-resistant activity of SO2 was 91% as tested according to Q / SH 1170 042-2015 standard, the strength of the vanadium-based catalyst C9 was 120 N / cm, and the average pore size of the catalyst was 480 nm.
[0104] Example 10
[0105] The vanadium-based catalyst C10 was prepared according to the method of Example 1, except that sodium sulfate was not added. The rest was the same as Example 1.
[0106] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 87%, the strength of the vanadium-based catalyst C10 is 80 N / cm, and the average pore size of the catalyst is 248 nm.
[0107] Embodiment 11
[0108] The vanadium-based catalyst C11 was prepared according to the method of Example 1, except that cesium sulfate was not added. The rest was the same as Example 1.
[0109] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 86.5%, the strength of the vanadium-based catalyst C11 is 90 N / cm, and the average pore size of the catalyst is 252 nm.
[0110] Example 12
[0111] The vanadium-based catalyst C12 was prepared according to the method of Example 1, except that cesium sulfate and sodium sulfate were not added, and the rest was the same as Example 1.
[0112] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 86%, the strength of the vanadium-based catalyst C12 is 75N / cm, and the average pore size of the catalyst is 255nm.
[0113] Embodiment 13
[0114] The vanadium-based catalyst C13 was prepared according to the method of Example 1, except that water vapor was not introduced into the calcination inlet for calcination at 650° C. for 1 h. The rest was the same as Example 1.
[0115] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 86.2%, the strength of the vanadium-based catalyst C13 is 85 N / cm, and the average pore size of the catalyst is 105 nm.
[0116] Comparative Example 1
[0117] The vanadium-based catalyst D1 was prepared according to the method of Example 1, except that the modified diatomaceous earth S1 obtained in Preparation Example 1 was replaced by the diatomaceous earth before modification in Preparation Example 1, that is, the diatomaceous earth was not modified, and the rest was the same as Example 1.
[0118] According to the Q / SH 1170 042-2015 standard, the heat-resistant activity of SO2 is 86%, and the strength of the vanadium-based catalyst D1 is 52 N / cm.
[0119] Application Examples
[0120] The catalysts obtained in Examples 1-13 and Comparative Example 1 were applied to waste acid cracking gas (dust content 1-2 mg / Nm 3 ) In the sulfuric acid production unit, the inlet temperature is 390°C, SO2 is converted into SO3 and finally condensed into commercial sulfuric acid with w(H2SO4) of 98%-99.2%. The results are shown in Table 1.
[0121] Table 1
[0122]
[0123] It can be seen from the results in Table 1 that the loading amount of the porous catalyst obtained by Examples 1-13 of the present invention is significantly smaller than the loading amount of the catalyst obtained by Comparative Example 1. Under the premise of the same catalyst loading amount, the pressure drop of the sulfuric acid device is greatly reduced, and the total conversion rate of SO2 is guaranteed. At the same time, the method of the present invention greatly improves the strength of the catalyst.
[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A vanadium-based catalyst, characterized in that: The vanadium-based catalyst comprises modified diatomite and an active component and a co-active component supported on the modified diatomite; wherein the crystalline SiO2 content of the modified diatomite is not less than 90%, the active component comprises vanadium pentoxide, and the co-active component comprises potassium sulfate.
2. The vanadium-based catalyst according to claim 1, wherein The average particle size of the modified diatomaceous earth is 0.3-1 μm; Preferably, the preparation method of the modified diatomite comprises: separating and purifying the diatomite in a hydrocyclone separator to obtain diatomite powder, and then first calcining the diatomite powder to obtain modified diatomite; Preferably, the diatomaceous earth is of the genus Melosomum; more preferably, the diatomaceous earth is selected from one or more of Zhejiang diatomaceous earth, Yunnan diatomaceous earth and Changbai diatomaceous earth; Preferably, the shell of the modified diatomaceous earth is a hollow cylinder, the shells are connected by small thorns on the periphery of the shell to form a chain-like group, and the holes on the cylinder surface are connected to the central hole.
3. The vanadium-based catalyst according to claim 1 or 2, wherein In the vanadium-based catalyst, the molar ratio of potassium element to vanadium element is 2-3.
9.
4. The vanadium-based catalyst according to any one of claims 1 to 3, wherein The vanadium-based catalyst further comprises a promoter, and the promoter is selected from one or more of rubidium sulfate, cesium sulfate and sodium sulfate.
5. The vanadium-based catalyst according to claim 4, wherein Based on the total weight of the catalyst being 100%, the vanadium-based catalyst comprises: 60-75wt% of modified diatomaceous earth, 6-8.5wt% of vanadium pentoxide, 12-30wt% of potassium sulfate, 3.5-10wt% of an auxiliary agent and 0.5-2.5wt% of a binder; Preferably, based on 100% of the total weight of the catalyst, the vanadium-based catalyst comprises: 65-70wt% of modified diatomaceous earth, 6.5-8wt% of vanadium pentoxide, 15-22wt% of potassium sulfate, 4-8wt% of an auxiliary agent and 1-2wt% of a binder; Preferably, the binder is selected from one or more of montmorillonite, attapulgite and methyl cellulose.
6. The vanadium-based catalyst according to any one of claims 1 to 5, wherein The radial crushing resistance of the vanadium-based catalyst is ≥70N / cm, and the abrasion rate is ≤3%; Preferably, the vanadium-based catalyst is a plum blossom-shaped porous catalyst with 3-10 pores.
7. A method for preparing a vanadium-based catalyst, characterized in that: The preparation method comprises: (1) separating and purifying diatomaceous earth in a hydrocyclone separator to obtain diatomaceous earth powder, and subjecting the diatomaceous earth powder to a first calcination to obtain modified diatomaceous earth; (2) neutralizing vanadium water prepared with potassium hydroxide and vanadium pentoxide with sulfuric acid to obtain a reaction product; (3) The reaction product obtained in step (2) is mixed with the modified diatomaceous earth, optional auxiliary agents and adhesives, and kneaded, extruded, dried and second calcined to obtain a vanadium-based catalyst.
8. The preparation method according to claim 7, wherein: The crystalline SiO2 content of the modified diatomite is not less than 90%; And / or, in the vanadium water of step (2), the molar ratio of potassium element to vanadium element is 2-3.9; And / or, the mass ratio of the modified diatomaceous earth, the auxiliary agent and the adhesive is 60-75:3.5-10:0.5-2.5; And / or, the mass ratio of the modified diatomaceous earth to vanadium pentoxide is 60-75:6-8.
5.
9. The preparation method according to claim 7 or 8, wherein: The processing capacity of the hydrocyclone separator is 0.25-2.5m 3 / h, slurry inlet pressure 0.2-1MPa, classification fineness 0.3-1μm; and / or, the first calcination temperature is 350°C-500°C, and the time is 1-2h; And / or, the temperature of the second calcination is 580°C-650°C, and the time is 1-2h; preferably, the second calcination is carried out in a vertical tubular furnace and water vapor is continuously and evenly introduced into the calcination inlet.
10. The preparation method according to any one of claims 7 to 9, wherein: The diatomaceous earth is of the genus Melosomum; preferably, the diatomaceous earth is selected from one or more of Zhejiang diatomaceous earth, Yunnan diatomaceous earth and Changbai diatomaceous earth; And / or, the auxiliary agent is selected from one or more of rubidium sulfate, cesium sulfate and sodium sulfate; And / or, the binder is selected from one or more of montmorillonite, attapulgite and methyl cellulose.
11. Use of the vanadium-based catalyst according to any one of claims 1 to 6 or the vanadium-based catalyst prepared by the preparation method according to any one of claims 7 to 10 in wet-process sulfuric acid production.
12. A method for preparing wet sulfuric acid, characterized in that: In the presence of the vanadium-based catalyst described in any one of claims 1 to 6 or the vanadium-based catalyst prepared by the preparation method described in any one of claims 7 to 10, SO2 in the raw gas is catalytically oxidized to generate SO3, which is then condensed to obtain concentrated sulfuric acid.
13. The method according to claim 12, wherein: The volume percentage of SO2 in the raw gas is 1-9%; And / or, the raw gas is waste acid cracking gas or acid gas; preferably, the acid mist content of the waste acid cracking gas is less than 0.11 g / Nm 3 , mineral dust content <0.01g / Nm 3 ; And / or, the inlet temperature of the raw gas is 370°C-440°C And / or, the filling factor of the vanadium-based catalyst in the wet sulfuric acid production device is 500 L / (t·d).
Citation Information
Patent Citations
Purifying process of diatomaceous earth through flocculation and magneto-seperation by specific gravity
CN1045252A
Vanadium-based catalyst and preparation method therefor
CN111065458A
Method for preparing vanadium catalyst
CN1927453A
Cited By
Vanadium-based catalyst for sulfur dioxide conversion in waste acid treatment and preparation method thereof
CN121198280A
Vanadium-based catalyst for conversion of sulfur dioxide in waste acid treatment and preparation method thereof
CN121198280B
Preparation method of cesium-rubidium salt synergistically modified sulfur dioxide oxidation catalyst
CN122098619A
Vanadium-based catalyst, and preparation method therefor and use thereof
EP4744771A1